2021
DOI: 10.1080/07391102.2021.1933594
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of protein stability and allosteric interaction networks in distinct conformational forms of the SARS-CoV-2 spike D614G mutant: reconciling functional mechanisms through allosteric model of spike regulation

Abstract: In this study, we used an integrative computational approach to examine molecular mechanisms underlying functional effects of the D614G mutation by exploring atomistic modeling of the SARS-CoV-2 spike proteins as allosteric regulatory machines. We combined coarse-grained simulations, protein stability and dynamic fluctuation communication analysis with network-based community analysis to examine structures of the native and mutant SARS-CoV-2 spike proteins in different functional states. Through distance fluct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 114 publications
(150 reference statements)
1
11
0
Order By: Relevance
“…We also point out that our simulation of the WT spike can, by fiat, only identify the residue to be mutated, but not the amino acid to which the residue will be mutated. However, both experimental and computer simulation studies have already established that D614G, A570D, and a few other mutations transform the dynamics of the RBD and favor an "up" state (54,55,59,61,72). In the current work, we highlighted a set of residues which show high correlation with RBD opening motion.…”
Section: Concluding Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…We also point out that our simulation of the WT spike can, by fiat, only identify the residue to be mutated, but not the amino acid to which the residue will be mutated. However, both experimental and computer simulation studies have already established that D614G, A570D, and a few other mutations transform the dynamics of the RBD and favor an "up" state (54,55,59,61,72). In the current work, we highlighted a set of residues which show high correlation with RBD opening motion.…”
Section: Concluding Discussionmentioning
confidence: 71%
“…The D614G mutant prefers the one RBD "up" state ∼7 times more than the "three-down" configuration, while they are equally likely in the WT strain (54). The specific role of the D614G mutation was recently also established by coarse-grained MD study (72). Our model predicted the D614 residue as a key player in RBD dynamics from physicsbased atomistic simulations without any prior knowledge of the mutation profile of the spike.…”
Section: Concluding Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Lineage B.1.351 4 was first identified in November 2020 in South Africa and is characterized by two additional substitutions of likely significance in RBD, namely, K417N and E484K. The former is predicted to disrupt a salt bridge with D30 of ACE2, a characteristic of SARS-CoV-2 in distinction to severe acute respiratory syndrome coronavirus (SARS-CoV-1), but may not impact on binding, whereas the latter, which might disrupt the interaction of RBD with K31 of human ACE2, may enhance ACE2 binding 2,5 . On 1 March 2021, this lineage accounted for 5% of all current sequences globally, and 100% of those identified in South Africa.…”
mentioning
confidence: 99%
“…These studies showed that examining allosteric behavior of the SARS-CoV-2 S proteins may be useful to uncover functional mechanisms and rationalize the growing body of diverse experimental data. In particular, using an atomistic-based model of signal transmission in the SARS-CoV-2 S proteins, we determined that the D614G mutation can exert its effect through allosterically induced changes on stability and communications in the residue interaction networks [70,71]. Previous computational studies also identified residues that exhibit long-distance couplings with the RBD opening that included sites harboring functional mutations D614G and A570D shared across SARS-CoV-2 S protein variants [59].…”
Section: Introductionmentioning
confidence: 99%